Kajian al-Qur’an dalam Tradisi Pesantren: Telaah atas Tafsir al-Iklîl fî Ma’ânî al-Tanzîl - Supriyanto Supriyanto (Universitas Darussalam Gontor, 2016)
This paper aims to study the writing of the interpretation of the Qur’an around Islamic boarding school. The main topic of discussion is about the book written by a Moslem scholar from Pesantren al-Balagh, Bangilan, which is titled by Tafsîr al-Iklîl fî Ma’âni al-Tanzîl. It’s written by KH. Misbah Mustafa. This study proves that the tradition developed at Islamic boarding schools has significant influence in writing interpretation of the Qur’an. The book showed us the relation between Islamic traditions and the interpretation of the Qur’an. There are some values of Islamic boarding school tradition mentioned in this book like the use of script Java-Arab (Pegon) as the identity of the interpretation, language stratification in the interpretation, contextual interpretation based on the Islamic boarding school tradition, and many stories found as the media of the interpretation. In general, through his book, KH. Misbah Mustafa had contributed giving new variation of interpretation between Moslem scholars in Islamic boarding school, whether they were living in the same time or as succeeding generations. Through this work, we could see that the Moslem scholar who is living in Islamic boarding schools also has high level of academic wealth in the tradition of interpretation of the Qur’an. Therefore, KH. Misbah Mustafa has shown us that a Moslem scholar also has the ability to write a comprehensive interpretation book. Thus, this work should be equated with the works of interpretation of the Qur’an that had been written by other Moslem scholars of Nusantara.